Catastrophic ice shelf collapse along the NW Laurentide Ice Sheet highlights the vulnerability of marine-based ice margins. (15th June 2022) - England, J.H.; Coulthard, R.D.; Furze, M.F.A.; Dow, C.F.
Abstract: We document the unparalleled depositional and chronological record of an 80, 000 km 2 ice shelf from the former Laurentide Ice Sheet whose advance and retreat spanned only ∼400 years (11.6–11.2 cal ka BP). Its catastrophic breakup (∼150 years; 11.3–11.2 cal ka BP) coincided with a rapidly warming atmosphere and ocean, paralleling reported conditions impacting the ongoing evolution of marine-based margins of Antarctica and Greenland. Our record highlights the instability of the NW Laurentide Ice Sheet whose marine-based ice streams and ice shelves retreated in channels of intermediate depth (400–600 m) that lack reverse slopes, suggesting that current ice dynamics models may underestimate the sensitivity of similar margins in Antarctica to ongoing global warming. Our reconstruction is based on > 700 km of coastal field surveys complemented by radiocarbon dates stratigraphically encompassing the full lifespan of the former Viscount Melville Sound Ice Shelf. Notably, this detailed record demonstrates that large ice shelves can be removed rapidly, cautioning against dismissing predictions of possible 21st century mean-sea-level rise >1 m derived from the ongoing retreat of marine-based ice sheets. We emphasize that during the last deglaciation of the western Canadian Arctic Archipelago, prominent ice streams transitioned into ice shelves whose depositional landforms are pervasive, demonstrating their pivotal role in the evisceration of the NW Laurentide Ice Sheet. The VMSIS provides an exceptionally detailed geological record whose tightly constrained chronology of growth, maintenance and breakup serves as an instructive example for those modern marine-based margins whose instability is being investigated to address estimates of possible future sea level rise. Highlights: The Viscount Melville Sound Ice Shelf, western Arctic Canada, advanced rapidly at the end of the Younger Dryas covering 80, 000 km 2 . Its exceptional depositional record onlaps coastlines for 700 km and widespread radiocarbon dates on marine shells document its full lifespan. The ice stream/ice shelf system spans only 400 years from initial advance to full removal. Removal of the ice stream/ice shelf system took only 150 years, forced by a warming atmosphere and ocean. This record shows that marine-based ice margins can retreat rapidly in intermediate water depths lacking reverse bedrock slopes.